REGENERATIVE PERIODONTAL THERAPY: ESSENTIAL CONCEPTS - Soares, Kaio Henrique; Martins, Olga Beatriz Lopes; Leite, Mariana Botelho; Alves, Sâmia Francy Ferreira; Lopes, Maria Rita Lima; Santos, Jefferson Aguiar; Paulino, Gabriela Leite; Soares, Célio Leone Ferreira (Seven Editora, 2026)
Regenerative Periodontal Therapy aims to restore periodontal tissues lost due to disease, promoting the formation of new cementum, periodontal ligament, and alveolar bone. Unlike simple repair, regeneration seeks to recover the original structure and function of the periodontium, improving dental prognosis and reducing the progression of periodontal disease. Therapeutic success depends on clot stability, selective cell exclusion, and proper root surface management. Several biomaterials and techniques can be used, such as bone grafts, membranes for guided tissue regeneration, and enamel matrix derivatives, with intraosseous defects being the most favorable for regeneration. Biofilm control, adequate surgical planning, and postoperative follow-up are fundamental for predictable and lasting results.